The trial of the templars - Barber, Malcolm (Cambridge University Press, 2006)
The participants -- The arrests -- The papal intervention -- The papal and episcopal inquiries -- The defence of the order -- The end of resistance -- The charges -- The trial in other countries -- The suppression